2018
DOI: 10.3390/socsci7070118
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Development Initiatives on Low-Income Households in Kelantan, Malaysia

Abstract: Abstract:To improve the socio-economic condition of low-income households, underlying organizations offer a variety of products and services such as access to working capital and training programs. This study examined the impact of access to working capital and training programs on household income and economic vulnerability among participants of AIM, TEKUN, and LKIM in Kelantan, Malaysia. Adopting a cross-sectional design, data were collected randomly from 450 micro-entrepreneurs living in seven districts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Microfinance institutions also offer non-financial facilities, particularly development training programs that are critical to achieving household socio-economic outcomes [26]. Literature indicates that training programs are an effective source of knowledge and these significantly influence business performance.…”
Section: Microfinance Non-financial Servicesmentioning
confidence: 99%
“…Microfinance institutions also offer non-financial facilities, particularly development training programs that are critical to achieving household socio-economic outcomes [26]. Literature indicates that training programs are an effective source of knowledge and these significantly influence business performance.…”
Section: Microfinance Non-financial Servicesmentioning
confidence: 99%
“…This shows that that literacy rates among the fishermen population in Muda river basin is high (91.3%) and the highest-level education in the communities is Form 6 or Diploma. According to Mustapa et al (2018), poverty in Malaysia is based on the PLI, poverty line income (Malaysian absolute poverty line), which is a quantitative money metric measure. In Peninsular Malaysia, PLI for the poor in the rural area is RM870, whereas PLI for hard-core poor is RM 580 (Table 03).…”
Section: Educational Level Of Inland Fishermenmentioning
confidence: 99%
“…Furthermore, Barney (1991) suggests that a firm’s value creation process solely lies in the owner-manager’s ability in acquiring the resources. Therefore, fitting into the Barney’s RBV and based on prior studies that focused on micro-entrepreneurship within a similar context, it can be assumed that entrepreneurial competencies of owner-managers of firms that identify and acquire resources can lead to superior firm performance, wherein such required competencies are triggered by relevant training programs (Zainol et al , 2017; Mustapa et al , 2018a, 2018b; Al Mamun et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, an empirical study focusing on women micro-entrepreneurs in Malaysia by Zainol et al (2017) found that the participants of development programs, who received training apart from financial assistance, have higher level of entrepreneurial competencies. In a more recent study that involved Kelantanese micro-entrepreneurs, Mustapa et al (2018a) discovered that the number of hours spent on training programs positively affected household income, while negatively influenced their level of economic vulnerability. Particularly in light of microenterprises, training sessions, total number of training hours received, and center meetings or discussions attended displayed a significant impact on firm performance (Mustapa et al , 2018b).…”
Section: Introductionmentioning
confidence: 99%